Effects of row spacing, nitrogen, and mepiquat chloride application on yield and spatio‐temporal patterns of cotton bolls in the yellow river valley of China. (1st December 2020) - Yan, Wei; Li, Fangjun; Xu, Dongyong; Eneji, A. Egrinya; Du, Mingwei; Tian, Xiaoli; Li, Zhaohu
Abstract: Mechanical harvesting of cotton is an inevitable trend in China due to the current shortage of farm labor. Row spacings of spindle‐type pickers are adjustable between 76 and 102 cm. However, it is not clear which is better for cotton production in the Yellow River Valley. This field study was conducted under stalk incorporation during 2016–2018, and consisted of experiments of row spacing × nitrogen (N) and row spacing × mepiquat chloride (MC). A split‐plot with four replications was used; row spacings (76, 92 and 102 cm) were assigned as main plots at equal population of 90 000 plants ha −1, and N (0, 105, 210 kg ha −1 ) or MC rates (0, 140, 281 and 394 g ha −1 ) as subplots. The wider row spacings (92 and 102 cm) yielded as much as the narrower spacing (76 cm) in 2016 and 2018, but out‐yielded the latter in the wet year (2017) due to the greater number of bolls. Nitrogen application had marginal effects on cotton yield. Mepiquat chloride application increased lint yield by increasing boll weight in 2016–2017, but decreased yield by reducing boll number at the highest rate (394 g ha −1 ) in the dry year of 2018. Considering plants spaced 92 cm more resistant to lodging than those spaced 102 cm, we suggest the 92 cm spacing may be selected. In addition, the 105–210 kg N ha −1 and the 140–281 g MC ha −1 were recommended to balance N removal in seed cotton and get higher or stable yield, respectively. Core Ideas: The wider row spacings (92 and 102 cm) out‐yielded the narrower one (76 cm) in the wet year. Nitrogen (N) application had marginal effects on lint yield. Mepiquat chloride applied at 140–281 g ha −1 increased or did not affect yield in three years. Row spacing did not interact with N and MC to affect lint yield.